Tantangan Dan Strategi Kepemimpinan Kepala Sekolah Di Era Merdeka Belajar SDN 1 Lubuk Ketepeng - Marini Marini; Edi Harapan; Pahlawan Pahlawan (CV. Ulil Albab Corp, 2026)
This study examines the challenges and leadership strategies of the principal in implementing the Merdeka Belajar policy at SDN 1 Lubuk Ketepeng. It focuses not only on identifying obstacles but also on how the principal interprets, adapts, and applies the policy to align with the school’s context and characteristics. A descriptive qualitative approach was employed, with data collected through in-depth interviews, direct observations, document analysis, and a Likert-scale questionnaire distributed via Google Form. Findings reveal key challenges, including shifts in the learning paradigm requiring teacher creativity and autonomy, limited ICT skills among some educators, heavy administrative demands, and restricted access to continuous professional development. To address these challenges, the principal implemented strategies such as fostering teacher collaboration, conducting regular supervision and coaching, optimizing communication with parents and the school committee, and organizing internal digital literacy training. Questionnaire results from 16 respondents indicated a highly positive perception of the principal’s leadership, with an average score of 4.07 (81.4%). The study concludes that the principal’s leadership is adaptive and collaborative, yet further strengthening of teachers’ technical and professional competencies is needed to optimize Merdeka Belajar implementation. These findings provide practical insights for educational leadership in enhancing school performance under national policy reforms.